2019
DOI: 10.1111/nan.12569
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral T cells from multiple sclerosis patients trigger synaptotoxic alterations in central neurons

Abstract: 2020) Neuropathology and Applied Neurobiology 46, 160-170 Peripheral T cells from multiple sclerosis patients trigger synaptotoxic alterations in central neurons Aims: The crucial step in the pathogenic events that lead to the development and the progression of multiple sclerosis (MS) is the infiltration of autoreactive T cells in the brain. Data from experimental autoimmune encephalomyelitis (EAE) mice indicate that, together with microglia, T cells are responsible for the enhancement of the glutamatergic tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 34 publications
4
34
0
Order By: Relevance
“…Furthermore, it would be important to use valid experimental models to reveal functions strictly linked to a specific MS pathogenic mechanism. The application of chimeric ex vivo MS models (CSF MS or T-cell MS chimeric models, [ 39 , 104 , 105 ]), consisting in incubation of EVs derived from MS biofluids onto mouse brain slices, together with biochemical, molecular, and electrophysiological analysis, might represent a good tool to study EVs roles in MS pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it would be important to use valid experimental models to reveal functions strictly linked to a specific MS pathogenic mechanism. The application of chimeric ex vivo MS models (CSF MS or T-cell MS chimeric models, [ 39 , 104 , 105 ]), consisting in incubation of EVs derived from MS biofluids onto mouse brain slices, together with biochemical, molecular, and electrophysiological analysis, might represent a good tool to study EVs roles in MS pathology.…”
Section: Discussionmentioning
confidence: 99%
“…The MS brain is also affected by another degenerative but potentially reversible phenomenon, namely inflammatory synaptopathy. Clinical research using transcranial magnetic stimulation (TMS) [ 37 ], pre-clinical studies conducted on an EAE model [ 29 , 38 ], and more recently chimeric ex-vivo models [ 29 , 39 ] have highlighted the presence of an inflammation-dependent decrease in the gamma-aminobutyric acid (GABA) ergic tone and an increase in the glutamatergic transmission in several MS/EAE brain areas. Such a synaptic transmission unbalances results in a diffuse synaptic dysfunction and loss that is mediated by pro-inflammatory molecules released by peripheral immune system cells, microglia, and astroglia [ 29 , 37 ].…”
Section: Multiple Sclerosis: Clinical Features and Pathophysiologymentioning
confidence: 99%
“…TNF is a major proinflammatory cytokine with a crucial pathogenic role in MS [ 3 , 4 , 24 ], extensively investigated in humans and MS animal models. These studies clearly showed that TNF is able to promote synaptic hyperexcitability and excitotoxic neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Autoreactive T and B lymphocytes play a crucial role in disease pathogenesis [ 1 , 2 ]. T cells enter CNS and interact with local immune cells, initiating the inflammatory cascade that amplifies the immune response and leads to both excitotoxic synaptopathy and consequent brain damage [ 3 , 4 ]. Both CD4 + and CD8 + autoreactive T lymphocytes have been identified in demyelinating lesions [ 1 ] and have been related to the severity of axonal damage and inflammation [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…AMPA and KA receptors are involved in the pathological pathway of excitotoxicity, and an inhibition of these receptors can decrease EAE severity [24]. One reason for increased glutamate receptor activity in EAE could be that T cells either interfere directly with the receptors or enhance glutamate transmission through the release of tumor necrosis factor α (TNF-α) [165]. TNF-α also activates glutamate release from microglia which can further trigger excitotoxicity [166].…”
Section: Calcium and Excitotoxicitymentioning
confidence: 99%